2020
DOI: 10.34067/kid.0002352020
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Up Mitochondria in Diabetic Nephropathy

Abstract: Mitochondrial medicine has experienced significant progress in recent years and is expected to grow significantly in the near future, yielding many opportunities to translate novel bench discoveries into clinical medicine. Multiple lines of evidence have linked mitochondrial dysfunction to a variety of metabolic diseases, including diabetic nephropathy (DN). Mitochondrial dysfunction presumably precedes the emergence of key histologic and biochemical features of DN, which provides the rationale to explore mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 101 publications
(50 reference statements)
0
24
0
1
Order By: Relevance
“…Overall, there is a consensus that enhancing mitochondrial biogenesis in podocytes in the diabetic milieu is beneficial for renal function ( 64 , 65 ). Interestingly, thiazolidinediones are PGC-1α activators ( 59 ).…”
Section: Mitochondrial Biogenesis In Diabetesmentioning
confidence: 99%
“…Overall, there is a consensus that enhancing mitochondrial biogenesis in podocytes in the diabetic milieu is beneficial for renal function ( 64 , 65 ). Interestingly, thiazolidinediones are PGC-1α activators ( 59 ).…”
Section: Mitochondrial Biogenesis In Diabetesmentioning
confidence: 99%
“…The time course of mitochondrial dysfunction in the kidney has been documented in several experimental models of diabetic kidney disease (DKD) ( 6 , 7 ). For instance, it was found that mitochondrial changes in size and function preceded histological and biochemical changes associated with kidney damage and these mitochondrial changes evolved with DKD progression ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the most important physiological system for producing chemical energy stored as ATP from glucose, it is not surprising that mitochondria gained early attention as a possible target of diabetes and its micro/macrovascular complications. The time course of mitochondrial dysfunction in the kidney has been documented in several experimental models of diabetic kidney disease (DKD) (6,7). For instance, it was found that mitochondrial changes in size and function preceded histological and biochemical changes associated with kidney damage and these mitochondrial changes evolved with DKD progression (6).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation and mitochondrial dysfunction are increasingly recognized as important causes of renal diseases [13][14][15][16][17][18] . Kidney is the organ with the second highest oxygen consumption in our body; it is distinctly sensitive to mitochondrial dysfunction, which promotes kidney injury and inflammation 19,20 .…”
Section: Introductionmentioning
confidence: 99%